Domestic regulation and service trade liberalization - Mattoo, Aaditya; Sauvé, Pierre (Washington, DC : World Bank ; Oxford University Press, 2003)
This book addresses two key questions: What impact can international trade rules on services have on the design and pursuit of domestic regulatory decisions? How can such negotiations be harnessed to promote and consolidate domestic policy reform? This timely volume offers contributions from many of the world's leading experts on trade on services.
Includes bibliographical references and index.
rpm 09/09/16
Loans
Keywords: Service industries; International trade; Free trade